Quantum interference between photo-excited states in a solid-state Mott insulator - Wall, S; Brida, D; Clark, SR; Ehrke, H; Jaksch, D; Ardavan, A; Bonora, S; Uemura, H; Takahashi, Y; Hasegawa, T; Okamoto, H; Cerullo, G; et al. (2010)
By exciting with sub-10-fs 1.6-μm pulses the quasi-one-dimensional Mott insulator ETF2TCNQ, we observe prompt collapse of the Mott gap modulated by 24-THz oscillations of the gap, which are assigned to quantum interference between holon-doublon excitations. © 2010 Optical Society of America.